Employability in Online Higher Education: A Case Study - Silva, Ana Paula; Lourtie, Pedro; Aires, Luísa (International Review of Research in Open and Distributed Learning, 2013)
Over the past 15 years, learning in distance education universities has become more interactive, flexible, collaborative, and participative. Nevertheless, some accounts have highlighted the importance of developing more instrumental and standardized educational practices to answer the challenges of employability. In fact, the choice of skills that are important to learning communities and the labour market has been the subject of controversy because it involves heterogeneous motives among different groups. This paper compares the perceptions of employability skills in a sample of teachers from the Universidade Aberta and a sample of students who attend a local learning centre at this University. The research focused on the following dimensions: a) the most important employability skills, and b) the employability skills to be developed in online undergraduate degrees. To collect the required data, a questionnaire was prepared and applied to students and teachers, taking the theoretical model of Knight and Yorke (2006) as its main reference. In spite of the specificity of each group, the results revealed some similarities between students and teachers with regard to employability. The conclusions also highlighted the need to promote research on this matter in online education.